2016
DOI: 10.1016/j.bbapap.2016.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive proteomic analysis of canola leaf inoculated with a plant growth-promoting bacterium, Pseudomonas fluorescens, under salt stress

Abstract: Plant growth-promoting bacteria can improve the tolerance of canola to salt stress. To better understand the effects of plant growth-promoting bacterium on the protein profiles of canola under salt stress condition, proteomics was performed. Salt-sensitive (Sarigol) and -tolerant (Hyola308) canola cultivars were inoculated with Pseudomonas fluorescens FY32, and the protein profiles of canola leaves were compared using a PEG-fractionation method. Cluster analysis of canola cultivars based on a stress tolerance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 59 publications
2
38
0
Order By: Relevance
“…Similarly, another study reported high activity of SOD, GPX, and CAT as well as upregulation of Cu/Zn SOD in the leaves under 150 mM NaCl. Upregulation of Cu/Zn SOD has similarly been demonstrated for Hyola308 under 150 and 300 mM NaCl stress (Banaei-Asl et al 2016). All these studies provide evidence to confirm that tolerant cultivars show remarkably more ROS scavenging activity than sensitive cultivars (Banaei-Asl et al 2016;Heidari 2010;Yıldız et al 2015).…”
Section: Reactive Oxygen Species Scavenging Systemsupporting
confidence: 68%
See 3 more Smart Citations
“…Similarly, another study reported high activity of SOD, GPX, and CAT as well as upregulation of Cu/Zn SOD in the leaves under 150 mM NaCl. Upregulation of Cu/Zn SOD has similarly been demonstrated for Hyola308 under 150 and 300 mM NaCl stress (Banaei-Asl et al 2016). All these studies provide evidence to confirm that tolerant cultivars show remarkably more ROS scavenging activity than sensitive cultivars (Banaei-Asl et al 2016;Heidari 2010;Yıldız et al 2015).…”
Section: Reactive Oxygen Species Scavenging Systemsupporting
confidence: 68%
“…Upregulation of Cu/Zn SOD has similarly been demonstrated for Hyola308 under 150 and 300 mM NaCl stress (Banaei-Asl et al 2016). All these studies provide evidence to confirm that tolerant cultivars show remarkably more ROS scavenging activity than sensitive cultivars (Banaei-Asl et al 2016;Heidari 2010;Yıldız et al 2015). Furthermore, the role of glutathione synthesis in canola is defined as oxidative protective mechanism (Ruiz & Blumwald 2002).…”
Section: Reactive Oxygen Species Scavenging Systemsupporting
confidence: 57%
See 2 more Smart Citations
“…Studies on canola have indicated significantly increased proline contents in the root and leaves of both salt-tolerant and sensitive cultivars under salt stress, and comparatively more in tolerant cultivars than sensitive ones (Dolatabadian et al 2008;Xue et al 2009). Proteomic analysis of canola-tolerant cultivars indicated that the abundance of P5CS in the root and leaves are increased (Banaei-Asl et al 2015;Banaei-Asl et al 2016;Yıldız et al 2015). It has been shown that high accumulation of proline in canola attributes to activating its biosynthesis and preventing its degradation (Xue et al 2009).…”
Section: Proline Synthesismentioning
confidence: 99%